Analisis dan Perancangan Instalasi Penerangan Gedung Perpustakaan Universitas Negeri Manado - Abast, Kluivert; Kilis, Billy; Angmalisang, Harrychoon; Rapar, Jocke; Sangi, Nontje (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2023)
This study aims to analyze and design electrical lighting installations in the Unima library building that meet PUIL 2011 standards The data analysis technique used is inductive data analysis Inductive data analysis encourages researchers to solve certain cases by testing a theory The lighting installation design for the Manado State University Library building uses a formula to find the number of light points needed in lux units based on needs assuming the recommended lamp is 150 watts In book room 1 after rounding the lights needed in book room 1 are 13 In book room 2 after rounding the lights needed in book room 2 are 23 In book room 3 after rounding the lights needed in book room 3 are 26 lights In reading room 1 after rounding up the lights needed in reading room 1 are 12 In reading room 2 after rounding up the lights needed in reading room 2 are 13 In the administration room after rounding the lights needed in the administration room are 4 lights They are recommended in the admin room using 100 watts For direct lighting systems with bright coloured ceilings and walls the coefficient value is 50 65 < strong>< p>